ULTRASONOGRAPHIC VS VERNIER CALIPERIC EVALUATION OF TESTES AND ACCESSORY GLANDS IN ONGOLE (BOS INDICUS) BULLS - SRINIVAS, MANDA; NAIDU, K S; SREENU, MAKKENA; RAO, K BABU; SRILATHA, CH (The Indian Journal of Animal Reproduction, 2023)
Breeding soundness evaluation was performed on 8 Ongole bulls aged between 3 to 5 years. The testicular biometry was compared between ultrasonography verses vernier measurements and trans-rectal ultrasonography was performed to evaluate the accessory sex glands. The mean body condition score was 6.63 ± 0.18. The overall mean scrotal circumference was 34.63 ± 0.21 cm and, it had a significant positive correlation with biometry of scrotum and testes, testicular volume, testicular weight and ejaculate volume (P<0.05). The testicular dimensions varied significantly between bulls (P<0.01 ). The overall mean testicular length, breadth and thickness measured by vernier calipers were recorded as 10.87 ± 0.08, 5.63 ± 0.05 and 5.28 ± 0.03 cm, respectively. The predicted volume of each testis was 159.15 ± 2. 70 cm3 and the predicted testicular weight was 168.18 ± 2.86 gm. The overall mean testicular length, breadth and thickness measured by ultrasonography were 10.66 ± 0.07, 5.42 ± 0.05 and 5.05 ± 0.03 cm respectively. The predicted volume of each testis of a pair was 143.06 ± 2.47 cm3and the predicted testicular weight was 151.18 ± 2.61 gm. The overall means of the ultrasonographic dimensions of seminal vesicle, ampullae, prostrate body and cauda epididymis were recorded as 1.58 ± 0.05, 0.61 ± 0.02, 1.19 ± 0.03 and 2.59 ± 0.03 cm respectively with highly significant difference between the bulls (P<0.01 ).